Front antireflection film structure of solar cell, solar cell and cell module
By designing anti-reflective film structures with specific thickness and refractive index on the front of the solar cell, the problem of potential-induced attenuation of the solar cell module is solved, and the reliability and photoelectric conversion efficiency of the battery module are improved.
Patent Information
- Application Number
- CN202420167181.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Priority Date
- 2023-11-20
- Filing Date
- 2024-01-23
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2034-01-23
AI Technical Summary
During operation, solar cell modules are prone to potential-induced attenuation, which leads to deterioration of the passivation effect of the battery surface, reduces the filling factor, open circuit voltage and short circuit current of the battery cell, and thus leads to the power attenuation of the battery module, with the attenuation rate of up to 70%.
A front anti-reflection film structure of a solar cell is designed, including a first silicon oxide layer, a silicon nitride layer, a first silicon nitride layer, a second silicon nitride layer and a second silicon oxide layer stacked in sequence. By combining a specific thickness and a refractive index, the refractive index of the anti-reflection film is reduced, the light absorption rate is increased, the photoelectric conversion efficiency is improved, and the anti-reflection film structure is denser, so as to prevent water vapor from entering the inside of the battery.
While ensuring battery conversion efficiency, it improves the potential-induced attenuation phenomenon at the end of the battery module, improves the reliability of the battery module, effectively blocks sodium ions from enriching on the anti-reflection film, and suppresses the potential-induced attenuation phenomenon.
Smart Images

Figure CN222582889U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to the technical field of solar cells, in particular to a front anti-reflection film structure of a solar cell, a solar cell and a battery assembly. Background Art
[0002] With global warming and the increasing prominence of the energy crisis, solar energy as a renewable energy source is gradually becoming an important part of the global energy transformation. However, battery components will have performance degradation problems during operation, among which potential induced degradation (PID) is a common degradation phenomenon. There are two main reasons for the occurrence of potential induced degradation: first, because the battery components cannot be completely insulated, water vapor can enter the battery components during long-term use, resulting in leakage current, which in turn leads to a decrease in conductivity; second, because the sodium ions generated on the surface of the battery components move to the surface of the battery cell under the action of the external electric field and are enriched in the anti-reflection film, thus causing potential induced degradation. Potential induced degradation will cause the passivation effect of the battery surface to deteriorate, thereby reducing the fill factor, open circuit voltage and short circuit current of the battery cell, and then cause the power attenuation of the battery component, and the attenuation rate may be as high as 70%. Utility Model Content
[0003] Based on this, it is necessary to provide a front anti-reflection film structure for solar cells, solar cells, and battery modules to address the above problems. The front anti-reflection film structure can improve the potential induced attenuation phenomenon of the battery module while ensuring the battery conversion efficiency, thereby improving the reliability of the battery module.
[0004] A front anti-reflection film structure of a solar cell, comprising a first silicon oxide layer, a silicon nitride layer, a first silicon oxynitride layer, a second silicon oxynitride layer and a second silicon oxide layer stacked in sequence, wherein the second silicon oxide layer is a light incident side;
[0005] Wherein, the thickness of the first silicon oxide layer is 2nm-10nm, and the refractive index is 1.9-2.1;
[0006] The silicon nitride layer is composed of at least two layers of silicon nitride films, the refractive index of the silicon nitride film decreases from the side close to the first silicon oxide layer to the direction close to the first silicon nitride oxide layer, and the thickness of the silicon nitride film close to the first silicon oxide layer is 10nm-20nm, and the refractive index is 2.3-2.4, and the thickness of the silicon nitride film close to the first silicon nitride oxide layer is 20nm-30nm, and the refractive index is 2.0-2.2;
[0007] The first silicon oxynitride layer has a thickness of 5 nm to 15 nm and a refractive index of 1.8 to 1.95;
[0008] The second silicon oxynitride layer has a thickness of 5 nm to 15 nm and a refractive index of 1.7 to 1.85;
[0009] The second silicon oxide layer has a thickness of 5nm-15nm and a refractive index of 1.6-1.8.
[0010] In one embodiment, the thickness of the front anti-reflection film structure is 70nm-85nm, and the refractive index is 1.9-2.1.
[0011] In one embodiment, the silicon nitride layer has a thickness of 53 nm-57 nm.
[0012] In one embodiment, the silicon nitride layer includes a first silicon nitride film, a second silicon nitride film and a third silicon nitride film which are sequentially stacked on the surface of the first silicon oxide layer; wherein the first silicon nitride film has a thickness of 10nm-15nm and a refractive index of 2.3-2.35, the second silicon nitride film has a thickness of 14nm-17nm and a refractive index of 2.15-2.25, and the third silicon nitride film has a thickness of 20nm-25nm and a refractive index of 2.1-2.2.
[0013] In one embodiment, the first silicon oxide layer has a thickness of 7 nm to 10 nm and a refractive index of 1.9 to 2.0.
[0014] In one embodiment, the sum of the thicknesses of the first silicon oxynitride layer and the second silicon oxynitride layer is 20 nm-25 nm.
[0015] In one embodiment, the refractive index decreases from the silicon nitride layer to the second silicon oxide layer.
[0016] In one embodiment, the refractive index of the first silicon oxynitride layer is 1.85-1.95, and the refractive index of the second silicon oxynitride layer is 1.75-1.85.
[0017] A solar cell comprises the front anti-reflection film structure of the solar cell as described above.
[0018] A battery assembly comprising the solar cell.
[0019] The front anti-reflection film structure of the solar cell provided by the utility model can reduce the refractive index of the anti-reflection film on the one hand, thereby increasing the light absorption rate and improving the photoelectric conversion efficiency, and on the other hand, make the anti-reflection film structure more compact, prevent water vapor from entering the interior of the battery, and have excellent surface defect passivation effect, reduce surface recombination and junction recombination near the emitter, and effectively block sodium ions from being enriched on the anti-reflection film, thereby inhibiting the potential induced attenuation phenomenon.
[0020] Therefore, the front anti-reflection film structure can improve the potential induced decay phenomenon at the battery component end while ensuring the battery conversion efficiency, thereby improving the reliability of the battery component. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a schematic diagram of the front anti-reflection film structure of a solar cell provided in Example 1 of the utility model.
[0022] In the figure: 10, a first silicon oxide layer, 20, a silicon nitride layer, 201, a first silicon nitride film, 202, a second silicon nitride film, 203, a third silicon nitride film, 30, a first silicon oxynitride layer, 40, a second silicon oxynitride layer, 50, a second silicon oxide layer. DETAILED DESCRIPTION
[0023] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively with reference to the relevant embodiments below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art in the technical field of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0025] Combination Figure 1 As shown, the utility model provides a front anti-reflection film structure of a solar cell, comprising a first silicon oxide layer 10, a silicon nitride layer 20, a first silicon oxynitride layer 30, a second silicon oxynitride layer 40 and a second silicon oxide layer 50 which are stacked in sequence, wherein the second silicon oxide layer 50 is a light incident side.
[0026] Among them, the thickness of the first silicon oxide layer 10 is 2nm-10nm, and the refractive index is 1.9-2.1. In the utility model, the first silicon oxide layer 10 is arranged on the surface of the emitter. On the one hand, it can make the contact surface have good interface performance, which is more conducive to surface passivation. On the other hand, the first silicon oxide layer 10 contains a large amount of hydrogen and has good density, so that the passivation effect can be enhanced, and water vapor can be prevented from entering the battery. In addition, under the action of the negative bias electric field, electrons are emitted from the emitter and enter the anti-reflection film structure through the tunneling effect, so that sodium ions are combined with electrons to form neutral particles. Sodium ions are no longer enriched on the anti-reflection film due to the negative bias, which suppresses the potential induced decay phenomenon. Preferably, the thickness of the first silicon oxide layer 10 is 7nm-10nm, and the refractive index is 1.9-2.0.
[0027] In the present invention, the silicon nitride layer 20 is composed of at least two layers of silicon nitride film, and the refractive index of the silicon nitride film decreases gradually from the side close to the first silicon oxide layer 10 to the direction close to the first silicon nitride oxide layer 30, and the thickness of the silicon nitride film close to the first silicon oxide layer 10 is 10nm-20nm, and the refractive index is 2.3-2.4, and the thickness of the silicon nitride film close to the first silicon nitride oxide layer 30 is 20nm-30nm, and the refractive index is 2.0-2.2.
[0028] The silicon nitride film near the first silicon oxide layer 10 has a high refractive index and thus a high silicon content, so that the lattice structure of the silicon nitride is more compatible with the silicon substrate, the number of interface states at the SiN-Si interface is reduced, and the number of effective recombination centers is reduced, thereby improving the passivation effect of surface defects of the cell. The silicon nitride film near the first silicon oxynitride layer 30 can reduce the overall refractive index of the anti-reflection layer, which has the effect of reducing extinction and increasing light transmittance and light absorptivity.
[0029] In the present invention, the thickness of the first silicon oxynitride layer 30 is 5nm-15nm, and the refractive index is 1.8-1.95. The first silicon oxynitride layer 30 can reduce the reflectivity of the anti-reflection film. At the same time, the silicon nitride layer 20 and the first silicon oxynitride layer 30 have an excellent anti-reflection effect, so that the silicon wafer has excellent light absorption rate, and at the same time has excellent passivation effect and low interface state density, reducing surface recombination and junction region recombination near the emitter, thereby effectively blocking sodium ions from invading the solar cell and weakening the potential induced decay phenomenon.
[0030] In the present invention, the second silicon oxynitride layer 40 has a thickness of 5nm-15nm and a refractive index of 1.7-1.85. The second silicon oxynitride layer 40 can further reduce the reflectivity of the anti-reflection film structure, and enhance the passivation effect and improve the minority carrier lifetime by increasing the thickness of silicon oxynitride.
[0031] In the present invention, the thickness of the second silicon oxide layer 50 is 5nm-15nm, and the refractive index is 1.6-1.8. The second silicon oxide layer 50 can further reduce the reflectivity of the anti-reflection film structure and improve the photoelectric conversion efficiency of the battery.
[0032] Therefore, the front anti-reflection film structure of the present invention can reduce the refractive index of the anti-reflection film through the mutual cooperation between the first silicon oxide layer 10, the silicon nitride layer 20, the first silicon nitride oxide layer 30, the second silicon nitride oxide layer 40, and the second silicon oxide layer 50 of specific thickness and specific refractive index, thereby increasing the light absorption rate and improving the photoelectric conversion efficiency. On the other hand, it can make the anti-reflection film structure more compact to prevent water vapor from entering the interior of the battery. At the same time, it has an excellent surface defect passivation effect, which can reduce the surface recombination near the emitter and the junction area recombination, and can also effectively block the enrichment of sodium ions on the anti-reflection film, thereby inhibiting the potential induced attenuation phenomenon.
[0033] Furthermore, the front anti-reflection film structure can improve the potential induced decay phenomenon at the battery assembly end while ensuring the battery conversion efficiency, thereby improving the reliability of the battery assembly.
[0034] Preferably, the refractive index of the front anti-reflection film structure is 1.9-2.1, and the thickness of the front anti-reflection film structure is 70nm-85nm. By controlling the thickness and refractive index of the front anti-reflection film structure, the battery conversion efficiency can be further improved, and the potential induced decay phenomenon can be further improved.
[0035] In order to better control the thickness of the anti-reflection film structure, the thickness of the silicon nitride layer 20 is 53 nm-57 nm, or the sum of the thicknesses of the first silicon oxynitride layer 30 and the second silicon oxynitride layer 40 is 20 nm-25 nm.
[0036] In order to better adjust the thickness and refractive index of the silicon nitride layer 20, in one embodiment, the silicon nitride layer 20 includes a first silicon nitride film 201, a second silicon nitride film 202 and a third silicon nitride film 203 which are sequentially stacked on the surface of the first silicon oxide layer 10; wherein, the thickness of the first silicon nitride film 201 is 10nm-15nm, and the refractive index is 2.3-2.35, the thickness of the second silicon nitride film 202 is 14nm-17nm, and the refractive index is 2.15-2.25, and the thickness of the third silicon nitride film 203 is 20nm-25nm, and the refractive index is 2.1-2.2.
[0037] In order to achieve a better anti-reflection effect, in one embodiment, the refractive index decreases from the silicon nitride layer 20 to the second silicon oxide layer 50. Preferably, the refractive index of the first silicon oxynitride layer 30 is 1.85-1.95, and the refractive index of the second silicon oxynitride layer 40 is 1.75-1.85.
[0038] The present invention does not limit the method of forming the first silicon oxide layer 10, the silicon nitride layer 20, the first silicon nitride oxide layer 30, the second silicon nitride oxide layer 40 and the second silicon oxide layer 50, as long as the thickness and refractive index of the first silicon oxide layer 10, the silicon nitride layer 20, the first silicon nitride oxide layer 30, the second silicon nitride oxide layer 40 and the second silicon oxide layer 50 meet the requirements. In one embodiment, the first silicon oxide layer 10, the silicon nitride layer 20, the first silicon nitride oxide layer 30, the second silicon nitride oxide layer 40 and the second silicon oxide layer 50 are sequentially deposited by plasma enhanced chemical vapor deposition.
[0039] The utility model also provides a solar cell, which may be a PERC cell or a TOPCon cell. The solar cell includes the front anti-reflection film structure as described above, so that the solar cell has excellent conversion efficiency and resistance to potential induced degradation.
[0040] The utility model also provides a battery assembly comprising the solar cell. Since the solar cell has excellent resistance to potential induced degradation, the reliability of the battery assembly is improved.
[0041] Hereinafter, the front anti-reflection film structure of the solar cell, the solar cell, and the solar cell assembly will be further described through the following specific embodiments.
[0042] Example 1
[0043] The silicon wafer was placed in a double-boat coating furnace tube, and silane with a flow rate of 1000sccm and nitrous oxide with a flow rate of 4000sccm were introduced. The pressure was 130Pa, the power of the small boat was 7500W, the power of the large boat was 11000W, the pulse was on for 2ms, the pulse was off for 30ms, and the time was 20s, to generate a first silicon oxide layer with a refractive index of 1.9 and a thickness of 2nm.
[0044] Silane with a flow rate of 1500sccm and ammonia with a flow rate of 4000sccm were introduced into the coating furnace tube. The pressure was 210Pa, the small boat power was 7500W, the large boat power was 11000W, the pulse was on for 2ms, the pulse was off for 30ms, and the time was 50s, generating a first silicon nitride film with a refractive index of 2.3 and a thickness of 10nm.
[0045] Silane with a flow rate of 1000sccm and ammonia with a flow rate of 4000sccm were introduced into the coating furnace tube. The pressure was 210Pa, the small boat power was 9000W, the large boat power was 11000W, the pulse was on for 2ms, the pulse was off for 30ms, and the time was 100s, generating a second silicon nitride film with a refractive index of 2.15 and a thickness of 14nm.
[0046] Silane with a flow rate of 1000sccm and ammonia with a flow rate of 4000sccm were introduced into the coating furnace tube. The pressure was 210Pa, the small boat power was 9000W, the large boat power was 11000W, the pulse was on for 2ms, the pulse was off for 30ms, and the time was 100s, to generate a third silicon nitride film with a refractive index of 2.1 and a thickness of 20nm.
[0047] Into the coating furnace tube, silane with a flow rate of 1000sccm, ammonia with a flow rate of 4000sccm and nitrous oxide with a flow rate of 5000sccm were introduced, the pressure was 130Pa, the small boat power was 8000W, the large boat power was 11000W, the pulse was on for 2ms, the pulse was off for 30ms, the time was 100s, and a first silicon oxynitride layer 30 with a refractive index of 1.8 and a thickness of 5nm was generated.
[0048] Into the coating furnace tube, silane with a flow rate of 1000sccm, ammonia with a flow rate of 4000sccm and nitrous oxide with a flow rate of 5000sccm were introduced, the pressure was 130Pa, the small boat power was 8000W, the large boat power was 11000W, the pulse was on for 2ms, the pulse was off for 30ms, the time was 100s, and a second silicon oxynitride layer with a refractive index of 1.7 and a thickness of 5nm was generated.
[0049] Silane with a flow rate of 1000sccm and laughing gas with a flow rate of 10000sccm were introduced into the coating furnace tube, the pressure was 130Pa, the small boat power was 8000W, the large boat power was 11000W, the pulse was on for 2ms, the pulse was off for 30ms, the time was 80s, and a second silicon oxide layer with a refractive index of 1.6 and a thickness of 5nm was generated to obtain a front anti-reflection film structure of a solar cell. The total thickness of the front anti-reflection film structure was 61nm and the refractive index was 2.15.
[0050] Example 2
[0051] The silicon wafer was placed in a double-boat coating furnace tube, and silane with a flow rate of 2000sccm and nitrous oxide with a flow rate of 10000sccm were introduced. The pressure was 150Pa, the power of the small boat was 9000W, the power of the large boat was 13000W, the pulse was on for 5ms, the pulse was off for 60ms, the time was 50s, and the first silicon oxide layer with a refractive index of 2.1 and a thickness of 10nm was generated.
[0052] Silane with a flow rate of 3000sccm and ammonia with a flow rate of 10000sccm were introduced into the coating furnace tube, the pressure was 250Pa, the small boat power was 9000W, the large boat power was 14000W, the pulse was on for 5ms, the pulse was off for 60ms, the time was 150s, and the first silicon nitride film with a refractive index of 2.35 and a thickness of 15nm was generated.
[0053] Silane with a flow rate of 3000sccm and ammonia with a flow rate of 15000sccm were introduced into the coating furnace tube. The pressure was 150Pa, the small boat power was 11000W, the large boat power was 14000W, the pulse was on for 5ms, the pulse was off for 60ms, and the time was 300s, generating a second silicon nitride film with a refractive index of 2.25 and a thickness of 17nm.
[0054] Silane with a flow rate of 3000sccm and ammonia with a flow rate of 15000sccm were introduced into the coating furnace tube. The pressure was 150Pa, the small boat power was 11000W, the large boat power was 14000W, the pulse was on for 5ms, the pulse was off for 60ms, and the time was 300s, generating a third silicon nitride film with a refractive index of 2.2 and a thickness of 25nm.
[0055] Into the coating furnace tube, silane with a flow rate of 3000sccm, ammonia with a flow rate of 15000sccm and nitrous oxide with a flow rate of 15000sccm were introduced, the pressure was 150Pa, the small boat power was 11000W, the large boat power was 14000W, the pulse was on for 5ms, the pulse was off for 60ms, the time was 200s, and the first silicon oxynitride layer with a refractive index of 1.95 and a thickness of 15nm was generated.
[0056] Into the coating furnace tube, silane with a flow rate of 3000sccm, ammonia with a flow rate of 15000sccm and nitrous oxide with a flow rate of 15000sccm were introduced, the pressure was 150Pa, the small boat power was 11000W, the large boat power was 14000W, the pulse was on for 5ms, the pulse was off for 60ms, the time was 200s, and a second silicon oxynitride layer with a refractive index of 1.85 and a thickness of 15nm was generated.
[0057] Silane with a flow rate of 1000sccm and laughing gas with a flow rate of 10000sccm were introduced into the coating furnace tube, the pressure was 130Pa, the small boat power was 8000W, the large boat power was 11000W, the pulse was on for 2ms, the pulse was off for 30ms, the time was 150s, and a second silicon oxide layer with a refractive index of 1.8 and a thickness of 15nm was generated to obtain a front anti-reflection film structure of a solar cell. The total thickness of the front anti-reflection film structure was 112nm and the refractive index was 2.10.
[0058] Example 3
[0059] The silicon wafer was placed in a double-boat coating furnace tube, and silane with a flow rate of 2000sccm and nitrous oxide with a flow rate of 10000sccm were introduced. The pressure was 150Pa, the power of the small boat was 9000W, the power of the large boat was 13000W, the pulse was on for 5ms, the pulse was off for 60ms, the time was 50s, and the first silicon oxide layer with a refractive index of 2.1 and a thickness of 10nm was generated.
[0060] Silane with a flow rate of 3000sccm and ammonia with a flow rate of 10000sccm were introduced into the coating furnace tube, the pressure was 250Pa, the small boat power was 9000W, the large boat power was 14000W, the pulse was on for 5ms, the pulse was off for 60ms, the time was 150s, and the first silicon nitride film with a refractive index of 2.3 and a thickness of 11nm was generated.
[0061] Silane with a flow rate of 3000sccm and ammonia with a flow rate of 15000sccm were introduced into the coating furnace tube. The pressure was 150Pa, the small boat power was 11000W, the large boat power was 14000W, the pulse was on for 5ms, the pulse was off for 60ms, and the time was 300s, generating a second silicon nitride film with a refractive index of 2.15 and a thickness of 17nm.
[0062] Silane with a flow rate of 3000sccm and ammonia with a flow rate of 15000sccm were introduced into the coating furnace tube. The pressure was 150Pa, the small boat power was 11000W, the large boat power was 14000W, the pulse was on for 5ms, the pulse was off for 60ms, and the time was 300s, to generate a third silicon nitride film with a refractive index of 2.1 and a thickness of 25nm.
[0063] Into the coating furnace tube, silane with a flow rate of 3000sccm, ammonia with a flow rate of 15000sccm and nitrous oxide with a flow rate of 15000sccm were introduced, the pressure was 150Pa, the small boat power was 11000W, the large boat power was 14000W, the pulse was on for 5ms, the pulse was off for 60ms, the time was 200s, and the first silicon oxynitride layer with a refractive index of 1.95 and a thickness of 5nm was generated.
[0064] Into the coating furnace tube, silane with a flow rate of 3000sccm, ammonia with a flow rate of 15000sccm and nitrous oxide with a flow rate of 15000sccm were introduced, the pressure was 150Pa, the small boat power was 11000W, the large boat power was 14000W, the pulse was on for 5ms, the pulse was off for 60ms, the time was 200s, and a second silicon oxynitride layer with a refractive index of 1.8 and a thickness of 5nm was generated.
[0065] Silane with a flow rate of 1000sccm and laughing gas with a flow rate of 10000sccm are introduced into the coating furnace tube, the pressure is XPa, the small boat power is XW, the large boat power is XW, the pulse is on for 2ms, the pulse is off for 30ms, and the time is 50s. A second silicon oxide layer with a refractive index of 1.8 and a thickness of 5nm is generated to obtain a front anti-reflection film structure of a solar cell. The total thickness of the front anti-reflection film structure is 78nm and the refractive index is 2.08.
[0066] Example 4
[0067] Example 4 is carried out with reference to Example 1, except that: a first silicon oxide layer with a refractive index of 2.0 and a thickness of 7 nm is generated, and the total thickness of the front anti-reflection film structure is 66 nm and the refractive index is 2.10.
[0068] Example 5
[0069] Example 5 is carried out with reference to Example 1, except that: a first silicon oxynitride layer with a refractive index of 1.9 and a thickness of 10 nm is generated, a second silicon oxynitride layer with a refractive index of 1.8 and a thickness of 10 nm is generated, and the total thickness of the front anti-reflection film structure is 71 nm, and the refractive index is 2.00.
[0070] Comparative Example 1
[0071] Place the silicon wafer into the coating furnace tube, introduce silane with a flow rate of 3000sccm and ammonia with a flow rate of 10000sccm, the pressure is 250Pa, the small boat power is 9000W, the large boat power is 14000W, the pulse is on for 5ms, the pulse is off for 60ms, the time is 150s, and the first silicon nitride film with a refractive index of 2.4 and a thickness of 20nm is generated.
[0072] Silane with a flow rate of 3000sccm and ammonia with a flow rate of 15000sccm were introduced into the coating furnace tube. The pressure was 150Pa, the small boat power was 11000W, the large boat power was 14000W, the pulse was on for 5ms, the pulse was off for 60ms, and the time was 300s, generating a second silicon nitride film with a refractive index of 2.3 and a thickness of 30nm.
[0073] Silane with a flow rate of 3000sccm and ammonia with a flow rate of 15000sccm were introduced into the coating furnace tube. The pressure was 150Pa, the small boat power was 11000W, the large boat power was 14000W, the pulse was on for 5ms, the pulse was off for 60ms, and the time was 300s, to generate a third silicon nitride film with a refractive index of 2.05 and a thickness of 30nm.
[0074] Silane with a flow rate of 1000sccm and laughing gas with a flow rate of 10000sccm were introduced into the coating furnace tube, the pressure was 140Pa, the small boat power was 8000W, the large boat power was 11000W, the pulse was on for 2ms, the pulse was off for 30ms, the time was 150s, and a silicon oxide layer with a refractive index of 1.8 and a thickness of 15nm was generated, and a front anti-reflection film structure of a solar cell was obtained. The total thickness of the front anti-reflection film structure was 95nm and the refractive index was 2.05.
[0075] Test Case
[0076] The front anti-reflection film structure of the solar cell obtained in Examples 1-5 and Comparative Example 1 was made into a PERC cell module, the temperature was 85°C, the relative humidity was 85%, the frame of the module was connected to a positive voltage of 1500V and grounded, the output end of the module was short-circuited and connected to a negative voltage, defined as a voltage of 1500V, and the fill factor (FF), short-circuit current (Isc), open-circuit voltage (Uoc), maximum operating current (Imp), maximum operating voltage (Vmp), and maximum power (Pm) of the PERC cell were tested at 1500V using a CH340C environmental test box, a quality assurance PID special test power supply, a solar simulator, and an EL detector, and the potential induced decay rate after 192h was calculated. The calculation process is shown below, and the results are shown in Table 1.
[0077] Potential induced decay rate (%) = (initial maximum power - maximum power after 192 h) / initial maximum power × 100%.
[0078] Table 1
[0079]
[0080] According to Table 1, the front anti-reflection film structure of the solar cell obtained in Example 1 is made into a PERC cell, which has a 4% higher resistance to potential induced degradation than the PERC cell made of the front anti-reflection film structure of the solar cell obtained in Comparative Example 1. By comparing Examples 1-5 and Comparative Example 1, it can be seen that the front anti-reflection film structure of the solar cell obtained by the utility model can resist potential induced degradation while ensuring the cell efficiency, thereby improving the stability of the cell assembly.
[0081] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0082] The above-mentioned embodiments only express several implementation methods of the utility model, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the utility model patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the utility model, which all belong to the protection scope of the utility model. Therefore, the protection scope of the utility model patent shall be based on the attached claims.
Claims
1. A front anti-reflection film structure of a solar cell, characterized in that: It includes a first silicon oxide layer, a silicon nitride layer, a first silicon oxynitride layer, a second silicon oxynitride layer and a second silicon oxide layer which are stacked in sequence, wherein the second silicon oxide layer is on the light incident side; Wherein, the thickness of the first silicon oxide layer is 2nm-10nm, and the refractive index is 1.9-2.1; The silicon nitride layer is composed of at least two layers of silicon nitride films, the refractive index of the silicon nitride film decreases from the side close to the first silicon oxide layer to the direction close to the first silicon nitride oxide layer, and the thickness of the silicon nitride film close to the first silicon oxide layer is 10nm-20nm, and the refractive index is 2.3-2.4, and the thickness of the silicon nitride film close to the first silicon nitride oxide layer is 20nm-30nm, and the refractive index is 2.0-2.2; The first silicon oxynitride layer has a thickness of 5 nm to 15 nm and a refractive index of 1.8 to 1.95; The second silicon oxynitride layer has a thickness of 5 nm to 15 nm and a refractive index of 1.7 to 1.85; The second silicon oxide layer has a thickness of 5nm-15nm and a refractive index of 1.6-1.
8.
2. The front anti-reflection film structure of a solar cell according to claim 1, characterized in that: The thickness of the front anti-reflection film structure is 70nm-85nm, and the refractive index of the front anti-reflection film structure is 1.9-2.
1.
3. The front anti-reflection film structure of a solar cell according to claim 1 or 2, characterized in that: The thickness of the silicon nitride layer is 53nm-57nm.
4. The front anti-reflection film structure of a solar cell according to claim 3, characterized in that: The silicon nitride layer includes a first silicon nitride film, a second silicon nitride film and a third silicon nitride film which are sequentially stacked on the surface of the first silicon oxide layer; wherein the thickness of the first silicon nitride film is 10nm-15nm, and the refractive index is 2.3-2.35, the thickness of the second silicon nitride film is 14nm-17nm, and the refractive index is 2.15-2.25, and the thickness of the third silicon nitride film is 20nm-25nm, and the refractive index is 2.1-2.
2.
5. The front anti-reflection film structure of a solar cell according to claim 1 or 2, characterized in that: The first silicon oxide layer has a thickness of 7nm-10nm and a refractive index of 1.9-2.
0.
6. The front anti-reflection film structure of a solar cell according to claim 1 or 2, characterized in that: The sum of the thickness of the first silicon oxynitride layer and the second silicon oxynitride layer is 20 nm-25 nm.
7. The front anti-reflection film structure of a solar cell according to claim 1 or 2, characterized in that: The refractive index decreases from the silicon nitride layer to the second silicon oxide layer.
8. The front anti-reflection film structure of a solar cell according to claim 7, characterized in that: The refractive index of the first silicon oxynitride layer is 1.85-1.95, and the refractive index of the second silicon oxynitride layer is 1.75-1.
85.
9. A solar cell, characterized in that: A front anti-reflection film structure for a solar cell comprising the structure described in any one of claims 1 to 8.
10. A battery module comprising the solar cell according to claim 9.